The emotional intelligence development of future English language teachers - Tleubay, Sandugash T; Zhauynshiyeva, Zhazira B; Yessimkulova, Symbat S; Oralkanova, Zhaxylyk A; Akparova, Zhanna M; Nurpeissova, Assel; Kerimbekov, Toktar (International Journal of Innovative Research and Scientific Studies, 2023)
This article presents a methodology for intelligence development based on the premise of emotive units at the lexical-phraseological level and the emotive content of professional-oriented texts. The methodology of emotional intelligence development for future English language teachers is based on the provisions of the emotional-conceptual approach which includes three stages of teaching: nomination, description and expression of emotions by means of a foreign language. Each stage involves four levels of teaching: presentation, practice, production and assessment. The content of emotional intelligence in ELT includes: subject, procedure and outcome components. Our significant achievements are qualitative and quantitative indicators of the general communicative and professional-communicative aspects of students’ emotional intelligence development. The purpose of the article is to create a scientifically-based methodology for the emotional intelligence development of future foreign language teachers in the process of professionally-oriented education. The objectives of the article are to: substantiate the structural-content and functional characteristics of emotional intelligence; create a methodology for emotional intelligence development in foreign language teachers and define qualitative and quantitative indicators of emotional intelligence development.